Understanding Potential Brine Disposal Impacts of a Desalination Plant on Sharjah’s Coastal Waters - Alomar, Laila (2025)
A Master of Science thesis in Civil Engineering by Laila Alomar entitled, “Understanding Potential Brine Disposal Impacts of a Desalination Plant on Sharjah’s Coastal Waters”, submitted in November 2025. Thesis advisor is Dr. Serter Atabay and thesis co-advisor is Dr. Georgenes Cavalcante. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).